Online Purchase Intention Factors in Indonesian Millenial - Fitri, Rizka Annisa; Wulandari, Ririn (International Review of Management and Marketing, 2020)
Millennials live in an era that has high mobility and connected to the internet, thus impacting their desire to transact through an online platform. The results of this study indicate that online purchase intentions for Indonesian millennial are not affected by perceived of risk and social influences. But they still pay attention to the factors of perceived ease, usefulness, and price perceptions. The results of this study strengthen and develop the TAM theory by adding price perceptions, in addition to perceptions of ease and perceived usefulness in adopting the latest technology, online shopping at e-commerce Shopee Indonesia. That is the uniqueness of the result of this research. This research uses quantitative methods, with a sample of 260 respondents, determined using purposive sampling. Data were collected using an online questionnaire with an ordinal scale and analyzed using multiple linear analysis techniques assisted by software SPSS 23.0. Keywords: E-commerce, TAM, Price, Risk, Social influences, Online Purchase Intention JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.9852